2023
DOI: 10.3390/ma16247670
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure, Mechanical Properties, and Corrosion Resistance of Ag–Cu Alloys with La2O3 Fabricated by Selective Laser Melting

Xueyang Zhao,
Haiyan Zheng,
Xin Ma
et al.

Abstract: Ag and its alloys, when prepared by a selective laser melting (SLM) process, have a low density and poor overall performance due to their high reflectivity when the most commonly used laser (λ = 1060 nm) is used, and they have exorbitant thermal conductivity. These characteristics lead to the insufficient melting of the powders and severely limit the applications of additive manufactured silver alloys. To improve the absorption of the laser, as well as for better mechanical properties and higher resistance to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…It is difficult to find publications in the scientific literature discussing the impact of Cr and Ni additions on the structure and properties of laser-melted silver. Publications most often discuss the impact of laser melting on the structure and properties of pure silver and 925 silver [1,30,31] and investigations concerning silver alloys with the addition of Cu, C, and W [32], or the alloy Ag-Cu [2,33]. Investigations concerning the alloy Ag-Cu-Ge have also been published [34].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is difficult to find publications in the scientific literature discussing the impact of Cr and Ni additions on the structure and properties of laser-melted silver. Publications most often discuss the impact of laser melting on the structure and properties of pure silver and 925 silver [1,30,31] and investigations concerning silver alloys with the addition of Cu, C, and W [32], or the alloy Ag-Cu [2,33]. Investigations concerning the alloy Ag-Cu-Ge have also been published [34].…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the processing of Ag-Cu alloys using SLM (selective laser melting) inhibits the growth of columnar grains, which results in the refinement of the alloy [2].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation